CARICOM integration : the role of non-governmental organizations (NGOs) - Jackson, Rashleigh E. ([s.n.] [S.l.], 1997)
Discusses the role of NGOs in the current international environment. Describes the policy orientations of inter-governmental organizations including multilateral institutions, highlighting that of UNDP, as well as those of western bilateral donors, and assesses the impacts of these policies. Examines the ongoing debate on redefining the role of the state and what this means for NGOs. Analyzes the strengths and weaknesses of NGOs.